The Effect of Role Conflict and Job Stress on Turnover Intention in Nurses at Hasanuddin Damrah Manna Hospital, South Bengkulu Regency - Leni Corita; Karona Cahya Susena; Nurzam Nurzam (Penerbit Jurnal Indonesia, 2023)
Increased competitive pressure, accelerated technological change, and changes in demographic structure. Growing awareness and recognition of the increasingly important role of human resources in an organization. The aim of this research is to determine the effect of role conflict and work stress on turnover among nurses at Hasanuddin Damrah Manna Hospital, South Bengkulu Regency. The type of research used is quantitative. The data analysis methods used are multiple linear regression, coefficient of determination test, classical assumptions, and hypothesis testing.The results of multiple linear regression have the equation Y= 27.384-0.439 X1+0.156 X2+2.292 because the direction of the regression is positive, which means that if role conflict and work stress increase, turnover intentions will also increase. Role conflict is more influential than work stress, there is turnover intention because the role conflict regression value is -0.439 which is greater than the work stress regression value. Role conflict has a negative effect on turnover instruction, this is proven by the results of the t test showing t count > t table (-5.903 > 1.976) and a significance value of 0.000 < 0.05 meaning Ha is accepted and Ho is rejected. Job stress has a positive effect on turnover, this is proven by the results of the t test showing tcount > ttable (3.128 > 1.976) with a significant value of 0.000 < 0.05, meaning that H0 is rejected and Ha is accepted. Role conflict and work stress have a joint and significant effect on turnover among nurses at Hasanuddin Damrah Manna Hospital, South Bengkulu Regency, this is proven by the f test which shows the value of Fcount > Ftable (19.697 > 3.91) with a significance value of 0.000.